Clinical effectiveness of early treatment with hyperbaric oxygen therapy for severe late‐onset hemorrhagic cystitis after hematopoietic stem cell transplantation in pediatric patients. (10th December 2012) - Zama, Daniele; Masetti, Riccardo; Vendemini, Francesca; Di Donato, Ferruccio; Morelli, Alessandra; Prete, Arcangelo; Pession, Andrea
Abstract HC is a possible cause of morbidity and extended hospitalization after HSCT. Recent studies have reported the efficiency of HOT in adult patients who underwent allogeneic HSCT, but data in children are scarce. We report our single center experience with HOT in late‐onset HC after HSCT. Treatment with HOT consisted of daily sessions of breathing 100% O2 for a total of 75 min in the hyperbaric chamber with a minimum of eight sessions. HOT had been associated with a concomitant treatment with oral oxybutynin, hyperhydration and/or irrigation of the bladder through the catheter. Cidofovir had been administered based on the demonstration of viral infection. Between 2004 and 2011, 10 patients developed severe HC after a median of 26 days after HSCT. HOT was started after a median of six days since the clinical diagnosis of HC. After a median of 10 sessions of HOT, seven of 10 patients were in complete remission. HOT is a well‐tolerated procedure also in the pediatric setting. The early start of HOT might be effective in the treatment of HC offering advantages in terms of duration of symptoms and hospitalization.